"The Chant of Joy Dadaocheng": A STEAM Program for Art Talented Students. (May 2023) - Tuan, Shih-Chen; Kuo, Ching-Chih
A STEAM curriculum integrated with science, technology, engineering, art, and mathematics would help gifted students actively explore and integrate knowledges across the fields. In this study, a program "the Chant of Joy Dadaocheng" was designed by five teachers from various fields for students to explore historical culture, produce creative artworks, and present their performances. 15 students identified through the Identification Committee Board for gifted and talented students in Taipei City participated the program. After 5 days enrichment activities, a semi-structured interview, behavior observations, script, and artworks were collected to assess the learning outcomes. The data collected were coded, classified, and interpreted. The results indicated the participated students could derive new ideas from the historical and cultural context through artworks, props, music, choreography, stories, and sentiment; they were able to transform inspirations from learning experience into creative presentation; and exhibited cross-disciplinary literacy, creativity and problem-solving ability.